GEOVISUALISASI RUMAH GADANG BERBASIS WEBGIS STORYMAPS UNTUK STRATEGI PENGEMBANGAN PARIWISATA DI KAWASAN SERIBU RUMAH GADANG NAGARI KOTO BARU - Astuti, Juli; Endah Purwaningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Kawasan Seribu Rumah Gadang (KSRG) in Nagari Koto Baru, South Solok Regency, is a living heritage cultural landscape of Minangkabau vernacular architecture. Despite receiving an IDR 69.8 billion physical restoration investment from the Ministry of Public Works and Public Housing (PUPR), its geospatial and narrative information management remains conventional amid fluctuating tourist arrivals. This study aims to develop an interactive WebGIS StoryMaps-based geovisualization of Rumah Gadang, analyze its spatial pattern using Nearest Neighbor Analysis (NNA), and formulate sustainable tourism development strategies based on SWOT analysis and 2023–2025 tourist trends. The research method integrates field mapping (ground truthing) of 81 Rumah Gadang units (+1 Surau Menara), door-to-door interviews, ArcGIS Online spatial processing, NNA, and SWOT analysis. The results indicate that WebGIS StoryMaps successfully integrated attribute data for 82 objects, achieving a usability score of 88.4%. The NNA across the 69.27-hectare area yielded a Nearest Neighbor Ratio (NNR) of 52.532 (, ), confirming a Dispersed spatial pattern overall and by clan (Bariang, Durian, and Tigo Lareh). Furthermore, tourist volume surged significantly from 27,392 visitors in 2023 to 122,002 in 2025. The SWOT matrix produced 8 priority strategies, including integrating StoryMaps digital promotion with homestay edutourism (SO) and accelerating the conservation of 8 severely damaged Rumah Gadang units (WO).